In Situ Curing of a Polymer Film for Light-Proof Coring of Deep Rocks with Preservation of Rock Quality and Moisture - Zhiyu Zhao; Heping Xie; Tao Liu; Yifan Wu (Advances in Civil Engineering)
Deep in situ rock mechanic is of great significance for deep foundation research and engineering application. In order to explore the deep in situ mechanical law, it is necessary to maintain the in situ environment, which means to achieve fidelity coring. However, at present, there is a lack of method of deep rocks with quality-preserving, moisture-preserving, and light-proof to obtain deep rock specimens, making it difficult to obtain in situ scientific information of the core. In this study, we developed a novel in situ quality-preserving coring method of deep rocks based on an in situ film-forming process. In this method, a solution was covered on the core, and then a sealing polymer film was formed through crosslinking reaction. Organic montmorillonite and carbon black functional fillers were incorporated to further reduce the O2 and water vapor permeability and light transmittance of the polymer sealing film. The sealing film was characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. Compared to the neat silicone rubber film, the O2 and water vapor permeability and light transmittance of the sealing film were reduced by 81.2%, 84.4%, and 100%, respectively. In addition, the mechanical and thermal stability of the sealing film was excellent; it showed an elongation at a break of 98.0% and a tensile strength of 0.857 MPa. Moreover, a simulator was developed and the sealing film showed an excellent quality-preserving ability on the rock specimens. The significant improvement demonstrated that the method developed in this research may open up new opportunities for the development of the in situ quality-preserving coring method of deep rocks and construction of deep in situ rock mechanics.